Model pembelajaran kooperatif tipe round tabel berbantuan media tas pukaki terhadap keterampilan manulis puisi - galuh tanjung hutari; Arif Wiyat Purnanto; Putri Meinita Triana (Universitas Muhammadiyah Magelang, 2022)
Cooperative Learning Model Round Table Assisted by Pukaki Bag Media on Poetry Writing Skills in Fourth Grade Students of SD Negeri Girimulyo. This research uses Quasi Experimental Design with Time Series Design. The research subjects used a total sampling of fourth grade students. The sample used was 20 students. The data collection method was carried out using a performance test of 8. Test the construct validity of the poetry writing skill assessment sheet using expert opinion. The hypothesis was tested using the Wilcoxon matched pairs with the help of SPSS for Windows Cooperative learning model Round Table assisted by the media Bag Pukaki had a positive effect on poetry writing skills in fourth grade students of SD Negeri Girimulyo. This is evidenced by the results of the Wilcoxon matched pairs with the Asymp probability. Sig. (2-tailed) is 0.000<0.05. Based on the results of the analysis, there are differences in the average scores on the pretest 1,2,3, and 4, the average value is 56 stable and the posttest 1,2,3, and 4 results are stable at 79.